2021
DOI: 10.30794/pausbed.802882
|View full text |Cite
|
Sign up to set email alerts
|

Performans Değerlendi̇rme Hatalarina İli̇şki̇n Alginin Çalişan Sessi̇zli̇ği̇ Üzeri̇ndeki̇ Etki̇si̇

Abstract: Bu araştırmanın amacı, performans değerlendirme hatalarına ilişkin algının çalışan sessizliği üzerindeki etkisini incelemektir. Bu amaç, çalışanların performans değerlendirme süreçleriyle ilgili algıladıkları hataların onları örgüt içinde sessizliğe itebileceği varsayımına dayandırılmıştır. Araştırmada basit tesadüfi örnekleme yöntemi kullanılmıştır. Konya il merkezinde bulunan üç özel bankanın tesadüfi olarak seçilen 23 şubesinde anketler uygulanmıştır (n=131). Performans değerlendirme hatalarına ilişkin algı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The first of these is the employee's silence for the purpose of protecting his organization, while the other is his silence with the motivation to protect his colleagues (Brinsfield, 2009). Erbasi and Akdeniz (2021) according to the quantitative research method with the employees of private banks in order to determine the effect of the perception of performance appraisal error on employee silence, it was determined that the perception of performance appraisal error did not have a statistically significant effect on employee silence. Dogan and Kır (2018) found a significant relationship between organizational silence, employee performance and burnout syndrome as a result of the research conducted with hospital employees in accordance with the quantitative research method in order to examine the relationship between burnout syndrome, organizational silence and employee performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these is the employee's silence for the purpose of protecting his organization, while the other is his silence with the motivation to protect his colleagues (Brinsfield, 2009). Erbasi and Akdeniz (2021) according to the quantitative research method with the employees of private banks in order to determine the effect of the perception of performance appraisal error on employee silence, it was determined that the perception of performance appraisal error did not have a statistically significant effect on employee silence. Dogan and Kır (2018) found a significant relationship between organizational silence, employee performance and burnout syndrome as a result of the research conducted with hospital employees in accordance with the quantitative research method in order to examine the relationship between burnout syndrome, organizational silence and employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that add dimension (Cesur, Erkilet, & Taylan, 2015;Caliskan & Ozkoc, 2016;Khlaf & Tekin, 2021;Köksal, 2011;Ozgenel & Dursun, 2020). Similarly, in addition to the studies that deal with employee silence in an individual sense (Erbasi & Akdeniz, 2021;Erogluer & Erselcan, 2017;Sehitoglu & Zehir, 2010;Taskıran, 2011), it also deals with organizational silence in terms of organizational silence (Dogan & Kır, 2018;Tayfun & Catir, 2013) ıt is also possible to come across studies. However, no research has been found that examines and examines the effect of paternalistic leadership perception on employee silence in relation to personnel working in higher education institutions.…”
Section: Introductionmentioning
confidence: 99%